Dimensional Accuracy of Two Impression Materials Regarding Impression Technique and Pouring Time Using Cone Beam Computed Tomography Analysis - Hend Elkawash,; Salima Aoun,; Ehab Dauki,; Mohamed Algundi, (AlQalam Journal of Medical and Applied Sciences, 2025)
An ideal impression material should present with dimensional stability over long periods, allowing the precise production of cast models at any time. However, the materials commonly used in dental impressions present alterations in their dimensional behavior. This study amid to evaluates the effect of the Impression technique, Single step, two steps, and Impression pouring time on the dimensional accuracy of two different impression materials; polyvinyl siloxane impression material, and polyether impression material, using Cone Beam Computed Tomography (CBCT) analysis. Two commercially available impression materials were used in this study Polyvinyl siloxane (PVS)- Polyether (PE),30 standardized metal custom-made dies representing full veneer all ceramic crown preparation, and 30 perforated custom-made trays fabricated that be placed in the same position on the master die for each impression, each material divided into two groups each group (n 15)one group using two-step technique the other group one step technique For each group, specimens were subdivided according to the pouring time into three subgroups (5 samples); 1hour, 24hour, 7days. All samples submitted for CBCT for evaluation of their dimensions. There were no significant differences with PVS and PE, but the single step showed a significant difference in highest mean high compared to two steps. 1 hr. (4.96±0.01 μm) showed an insignificant difference on mean height compared to 24 hours (4.96±0.01 μm) and 7 days (4.90±0.01 μm) at p=0.791 for Single step.1 hr (4.86±0.01 μm) showed insignificant difference on mean height compared to 24 hours (4.85±0.01 μm) and 7 days (4.81±0.01 μm) at p=0.960 for Two steps for PVS. 1 hr (4.95±0.03 μm) showed insignificant difference on mean height compared to 24 hours (4.94±0.01 μm) and 7 days (4.89±0.01 μm) at p=0.100 for Single step. 24 hours (4.85±0.02 μm) showed significant difference on mean height compared to 1 hr (4.84±0.01 μm) and 7 days (4.80±0.01 μm) at p≤0.001 for two steps for PE. Polyvinyl siloxane and poly ether materials give high accurate stone dies. One-step impression taking technique give more accurate stone dies than the two-step technique. pouring time is very critical for PE impression materials. يجب أن تتميز مادة الطباعة المثالية بثبات أبعادي لفترات طويلة، مما يسمح بالإنتاج الدقيق للنماذج المصبوبة في أي وقت. ومع ذلك، فإن المواد المستخدمة بشكل شائع في طبعات الأسنان تظهر تغييرات في سلوكها البعدي. تهدف هذه الدراسة إلى تقييم تأثير تقنية الطباعة والخطوة الواحدة والخطوتين ووقت صب الطباعة على الدقة البعدية لمادتين مختلفتين للطباعات؛ مادة طباعة بولي فينيل سيلوكسان، ومادة طباعة بولي إيثر، باستخدام تحليل التصوير المقطعي المخروطي الشعاعي . تم استخدام مادتين تجاريتين للطباعات في هذه الدراسة بولي فينيل سيلوكسان-بولي إيثر ، و30 قالبًا معدنيًا قياسيًا مخصصًا يمثل تحضير التاج الخزفي الكامل، و30 صينية مثقبة مخصصة الصنع توضع في نفس الموضع على القالب الرئيسي لكل طباعة، كل مادة مقسمة إلى مجموعتين كل مجموعة (ن 15) مجموعة تستخدم تقنية الخطوتين والمجموعة الأخرى بتقنية الخطوة الواحدة لكل مجموعة، تم تقسيم العينات وفقًا لوقت الصب إلى ثلاث مجموعات فرعية (5 عينات)؛ ساعة واحدة، 24 ساعة، 7 أيام. جميع العينات المقدمة للتحليل التصوير المقطعي المخروطي الشعاعي لتقييم أبعادها. لم تكن هناك فروق ذات دلالة إحصائية مع بولي فينيل سيلوكسان وبولي إيثر ، لكن الخطوة الواحدة أظهرت فرقًا كبيرًا في أعلى متوسط ​​ارتفاع مقارنة بخطوتين. أظهرت ساعة واحدة (4.96 ± 0.01 ميكرومتر) فرقًا ضئيلًا في متوسط ​​الارتفاع مقارنة بـ 24 ساعة (4.96 ± 0.01 ميكرومتر) و 7 أيام (4.90 ± 0.01 ميكرومتر) عند p = 0.791 للخطوة الواحدة. أظهرت ساعة واحدة (4.86 ± 0.01 ميكرومتر) فرقًا ضئيلًا في متوسط ​​الارتفاع مقارنة بـ 24 ساعة (4.85 ± 0.01 ميكرومتر) و 7 أيام (4.81 ± 0.01 ميكرومتر) عند p = 0.960 لخطوتين لبولي فينيل سيلوكسان. أظهرت ساعة واحدة (4.95 ± 0.03 ميكرومتر) فرقًا غير مهم في متوسط ​​الارتفاع مقارنة بـ 24 ساعة (4.94 ± 0.01 ميكرومتر) و 7 أيام (4.89 ± 0.01 ميكرومتر) عند p = 0.100 للخطوة الواحدة. أظهرت 24 ساعة (4.85 ± 0.02 ميكرومتر) فرقًا كبيرًا في متوسط ​​الارتفاع مقارنة بساعة واحدة (4.84 ± 0.01 ميكرومتر) و 7 أيام (4.80 ± 0.01 ميكرومتر) عند p ≤ 0.001 لخطوتين لبولي إيثر. تعطي مواد بولي فينيل سيلوكسان وبولي إيثر قوالب حجرية عالية الدقة. تعطي تقنية أخذ الانطباع بخطوة واحدة قوالب حجرية أكثر دقة من تقنية الخطوتين. وقت الصب مهم للغاية لمواد طباعة بولي إيثر